KARAKTERISTIK FISIK KIMIA KITOSAN DARI CANGKANG RAJUNGAN (Portunus pelagius) MELALUI PROSES DEASETILASI DENGAN KONSENTRASI NaOH DAN WAKTU EKSTRAKSI SERTA DI APLIKASIKAN SEBAGAI BAHAN PENGAWET ALAMI PADA FILLET IKAN NILA - Izzah Nazilatul laili; Sukardi Sukardi; Noor Harini (Universitas Muhammadiyah Malang, 2019)
This research is done by 2 stages of making chitosan and applying on tilapia fish fillet. Objectives at stage 1 to determine the optimization of the difference in NaOH concentration (20%, 30%, 40%, and 50%) and time (30 minutes and 45 minutes) deacetylation extraction. while the objective at stage 2 to find out the effect of the difference of chitosan addition to natural preservative of tilapia fillet (0,5,5%, 1%, 1,5%, and 2%). Chitosan tests were performed on physicochemical properties (moisture content, ash content, protein content, solubility, viscosity, yield, and deacetylation degree) and fish fillet test (organoleptic and total plate count (TPC). The results showed that different concentrations of NaOH and extraction time deacetylation very significant effect on ash content, protein content, viscosity, solubility, degree of deacetylation, and yield. While the concentration of chitosan is applied to meat Tilapia fish fillet very significant effect on the preservation of the storage period. The best treatment in stage 1 is K3A2.